Europeans and the Media - Miconi, Andrea (Taylor & Francis, 2024)
This book investigates the relationship between the process of Europeanization – the expected rise of a common culture – and the role played by the media in the different regions. Drawing on a comparative model, the analysis is structured around frameworks related to the action of the media in shaping national identities; to the world-system theory, based on the hierarchization of geographical spaces; and to the regional patterns identified in scientific literature. The analysis draws on data collected from numerous markets and across a variety of media formats, to detect the geographical pattern that results from the diffusion of different technologies and cultural contents: the national, the regional, the European, and the global. This nuanced and insightful volume will interest students and scholars in the field of communication studies, European studies, and comparative media studies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non-Commercial (CC-BY-NC) 4.0 license.